PENGARUH MODEL PEMBELAJARAN ASSURE BERBANTUAN MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD INPRES TAMALANREA V KOTA MAKASSAR - Nurul Ulfa; Nurlina; A. Muafiah Nur (STKIP Subang, 2024)
This research is research that uses a quantitative approach with a Quasi Experimental type of research using a Non-Equivalent Pretest-Posttest Control Group research design. The design aims to determine the effect of the ASSURE learning model assisted by audiovisual media on the science learning outcomes of class IV students at SD Inpres Tamalanrea V, Makassar City. The independent variable in this research is the ASSURE learning model assisted by audiovisual media, while the dependent variable is science learning outcomes. The sample selection was carried out by Total Sampling type with the results of class IVa as the experimental group with a total of 28 students and class IVb as the control class with 29 students. Data collection techniques in research are observation, tests and documentation. Data was collected from administering tests in the cognitive domain and then analyzed descriptively and inferential statistics using the Independent Sample T-Test. The research results show that there are science learning outcomes with the material Changing Forms of Energy. This can be seen in the posttest average for the experimental class reaching 71.43. while the control class Posttest average reached 56.03. Based on hypothesis testing using the Independent Sample t test, the tcount value = 3.471, while the ttable value = 2.004. Based on the results obtained tcount > ttable (tcount = 3.471 > ttable = 2.004). Thus H0 is rejected and H1 is accepted.